Dynamic mechanical properties of Polyurethane Shape Memory Polymer Composites (SMPC) with different volume fractions of chopped strand mat glass fiber - Khiyon, Nor Hanim; Ali Rahman, Azerai; Arshad, Mohd Fadzil; Kamarudin, Mohd Khairul; A. Rahman, Sajith Totthatil (International Journal of Integrated Engineering, 2019)
Polyurethane shape memory polymer (SMP) are comparatively low in modulus. Hence, there is a need for incorporation of chopped strand mat glass fibers as reinforcing materials for the development of SMP composites (SMPC). In this study, glass fibers in different volume fractions which are 0%, 5%, 10%, 15% and 30% were used. The aim is to obtain the optimum volume fractions of glass fibers in SMPC based on the dynamic mechanical properties. The dynamic mechanical analysis (DMA) was carried out to determine the dynamic mechanical properties of the composite material. The dynamic parameters which reliance to temperature such as storage modulus (Eâ€™), loss modulus (Eâ€), damping factor (tan Î´), glass transition temperature (Tg) values and others will gives the data regarding the adhesion of fiber-matrix of the composite material. The result shows that upon the addition of reinforcing fibers, an improvement in storage modulus was obtained. The tan Î´ peak value were decrease when the fiber volume fractions were increased, which confirming the reinforcing effectiveness of glass fibers in SMPC. It was also observed that the (Tg) increase upon the addition of reinforcing glass fibers. Summarizing, 15SMPC was chosen as the optimum volume fractions of glass fibers in SMPC. The parameter of the damping vibration demonstrates main significance for civil applications for building reliability and performance enhancement. Besides, it can foresee the impacts of temperature and time towards the polymer viscoelastic performance under various conditions. This study will provide several information to determine its functional application in future research.